Active and reactive power conditioning using SMES devices with PMW-CSC: A feedback nonlinear control approach (2019)
The active and reactive power conditioning using superconducting magnetic energy storage (SMES) systems for low-voltage distribution networks via feedback nonlinear control is proposed in this paper. The SMES system is interconnected to ac grid using a pulsed-width modulated current source converter (PWM-CSC). The dynamical model of the system exhibits a nonlinear structure, which is eliminated by the application of a nonlinear feedback controller based of the expected behavior of the closed-loop system. The steady state analysis under time-domain reference frame to verify the stability properties on the proposed controller is used. The general control rules allow improving different objectives. The robustness and applicability of the proposed controller is tested considering unbalance and harmonic distortion in the voltage provided by the ac grid. It is also considered the possibility to use the SMES system with the proposed controller to compensate the active power oscillations of a wind-generator system. © 2019 The Authors